Excavations, evocations and invocations ... or how to deal with the holes in the dirt ... - Lewinsohn, Ana Caldas; Raquel, Fernanda [UNESP]; Silva (Kabilaewatala), Renata de Lima; Machado, Vinicius Torres [UNESP] (Univ Sao Paulo, Escola Comunicacoes & Artes, 2023)
In a moment of radical crisis caused by the COVID-19 pandemic institutions, in the face of the many graves opened to bury people whose deaths cannot even be ritualized, a group of four artists-teachers, of different institutions, question themselves about their own holes - the holes in history, in bodies, in living matter. The experience at a debate table with performative contours unfolds in this article, which, by means of a collective and performative writing, has as research subject the performing arts of our time, between the paradox of presence and absence, marked both by the political impacts and by their ability to not lose the power of magic, which connect you to other worlds.
Keywords: Death; Contemporary scene; Actuation; Crisis